Xenon exerts anti-seizure and neuroprotective effects in kainic acid-induced status epilepticus and neonatal hypoxia-induced seizure - Zhang, Yurong; Zhang, Mengdi; Liu, Songhua; Zhu, Wei; Yu, Jie; Cui, Yaru; Pan, Xiaohong; Gao, Xue; Wang, Qiaoyun; Sun, Hongliu (Experimental neurology, 2019)
Xenon is an inhalation anesthetic with a favorable safety profile, and previous studies have demonstrated its neuroprotective efficacy. However, whether xenon plays a role in the treatment of epilepsy or seizure remains unclear. This study aimed to investigate the role of xenon inhalation and explore the role of different xenon ratio gradients and different delayed treatment times in seizure models. Kainic acid (KA)-induced status epilepticus and neonatal hypoxia-induced seizure models were used in our study. Animals were subject to inhalation of xenon mixture for 60 min after the stimulation used to induce seizures. The control group was treated with 70% nitrogen/30% oxygen, as in previous reports. Behavioral changes, electroencephalography, neuronal injury, and learning and memory function were investigated in each group. The results indicate that xenon mixture significantly reduced the severity of seizures and neurodegeneration in both KA-induced status epilepticus and in neonatal mice with hypoxia-induced seizure. Moreover, treatment with different percentages of xenon (35%, 50%, or 70%), as well as at different intervention time points (immediately, delayed for 15 min, delayed for 30 min) after hypoxia induction significantly attenuated the severity of seizure and neuronal injury. Additionally, 50% or 70% xenon treatment, as well as immediate xenon treatment or with a delay of 15 min attenuated the learning and memory impairments induced by hypoxia. This study confirmed that xenon mixture exerts strong inhibitive effects in seizure and seizure-induced neuronal injury and defects of cognitive function. Moreover, the results suggest that intervention time window and percentage of xenon influence the efficacy of the xenon treatment. Our study supports that xenon inhalation represents a safe means to inhibit seizures and neuronal injury. [Display omitted] •Xenon mixture had strong anti-seizure and neuroprotective effects on KA-induced SE.•Xenon mixture exerts strong inhibitive effects in hypoxia-induced seizure.•Intervention time window influences the efficacy of the xenon treatment.•Percentage of xenon influences the efficacy of the xenon treatment.